The University as a Punisher: Control Mechanisms and Disciplinary Practices. The Disciplinary Board of the University of Athens (1911–1940) - Christodoulou, Angeliki; Gkonis, Vassilis; Karamanolakis, Vangelis (The Historical Review/La Revue Historique, 2023)
This article investigates the control mechanisms and practices of youth discipline in the twentieth century through the example of the archives of the University of Athens Disciplinary Board (1911–1940). The research extends from the introduction of the institution’s first set of regulations and the creation of the disciplinary board in 1911 up to 1940 and the beginning of World War II. The article starts with the assumption that control mechanisms and discipline practices do not remain constant over time; they change according to the spatial and temporal framework and the needs they serve at any given time. The basic working hypothesis is that their functioning and application within an educational institution are directly related to the behavioural patterns and values that the institution cultivated during its historical trajectory as well as to the complex and increasingly changing landscape of Greek society in the interwar period until 1940. At the same time, a comparison is attempted with similar examples to investigate the correlation between the disciplinary policy of the University of Athens and European and American universities.